Komunikasi Manajemen Krisis Dalam Penyusunan Daftar Pemilih Pemilu Tahun 2024 - Saepurohman, Asep; Komsiah, Siti (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
One of the most crucial stages in the general elections to be held in 2024 is the stage of compilingand establishing the voter list, this stage has a fairly complicated and complex problems. The stages ofcompiling the voter list require cooperation and support from various stakeholders in order to createaccurate and quality voter list data. Because the voter list is dynamic. In the process of preparing voterlists, there are two basic things that must be understood related to population data when viewed fromtheir position, namely there are data owners and data users. Who owns the data, of course, thegovernment, in this case the Ministry of Home Affairs, while the KPU is only a data user who does nothave access or authority to change it directly if problems are found regarding the data received.Problems that have the potential to become a source of crisis in the preparation of voter lists include theproblem of duplicating population data, the still recording of data on people who have died, and so on.So to explore KPU crisis management communication strategies in compiling the 2024 election voter list,in this study the researchers used a qualitative methodology with a case study method. In this study it wasfound that the crisis communication strategy implemented by the KPU was more towards deminish andbolstering strategies based on the Situational Crisis Communication (SCCT) theory. This strategyprovides a symbolic representation of an organization's historical performance and a relationshipbuildingapproach by bringing together the concepts of rhetoric, impression management, and imagerestoration to help predict how stakeholders will react to crisis.